SES : a soils expert system : a thesis presented in fulfilment of the requirements for the degree of Master of Science in Computer Science - Todd, E G (Massey University, 1988)
An Expert System Development Methodology is proposed, based on experimentation in developing a soils expert system (SES) which identifies a soil from incomplete field data. Tools for conceptual modeling of the soils domain are examined. The tools developed provide a means of recording the conceptual model of the knowledge from three different view points: the inference structures, the domain objects and the functional aspects. A review of the structures used in the knowledge bases of existing classification problems identifies eleven categories for grouping these structures. Using this information with the conceptual model, a detailed design of the knowledge base for SES is created. This design closely models those structures identified as important in the soils domain ensuring that important knowledge is represented explicitly.
Keywords: Expert systems (Computer science); Soil Science; Data processing